Triterpenoids CDDO-ethyl amide and CDDO-trifluoroethyl amide improve the behavioral phenotype and brain pathology in a transgenic mouse model of Huntington's disease - Stack, Cliona (2010)
Oxidative stress is a prominent feature of Huntington's disease (HD) due to mitochondrial dysfunction and the ensuing overproduction of reactive oxygen species (ROS). This phenomenon ultimately contributes to cognitive and motor impairment, as well as brain pathology, especially in the striatum. Targeting the transcription of the endogenous antioxidant machinery could be a promising therapeutic approach. The NF-E2-related factor-2 (Nrf2)/antioxidant response element (ARE) signaling pathway is an important pathway involved in antioxidant and anti-inflammatory responses. Synthetic triterpenoids, which are derived from 2-Cyano-3,12-Dioxooleana-1,9-Dien-28-Oic acid (CDDO) activate the Nrf2/ARE pathway and reduce oxidative stress in animal models of neurodegenerative diseases. We investigated the effects of CDDO-ethyl amide (CDDO-EA) and CDDO-trifluoroethyl amide (CDDO-TFEA) in N171-82Q mice, a transgenic mouse model of HD. CDDO-EA or CDDO-TFEA were administered in the diet at various concentrations, starting at 30 days of age. CDDO-EA and CDDO-TFEA upregulated Nrf2/ARE induced genes in the brain and peripheral tissues, reduced oxidative stress, improved motor impairment and increased longevity. They also rescued striatal atrophy in the brain and vacuolation in the brown adipose tissue. Therefore compounds targeting the Nrf2/ARE pathway show great promise for the treatment of HD.